ANALISIS PENGARUH KUALITAS LAYANAN JASA PADA PT. BANK TABUNGAN NEGARA (PERSERO) CABANG SAMARINDA - ., Rosiana (EKONOMIA, 2012)
Target of research is to know service variable like reliability, responsive, guarantee,empathy, and extant by together have an effect on signifikan to Satisfaction of Consumer at PT. Bank Tabungan Negara (persero) Cabang Samarinda and know service variable having an effect on dominant to Satisfaction of Consumer at PT. Bank Tabungan Negara (persero) in SamarindaKnown by equantion of doubled linear regression that is: Y=-1,538 + 0,226 X1 + 0,283 X2 Â + 0,329X3 + 0,349 X4 + 0,204 X5.Value correlation coefficient (R) 0,715, its meaning there are strong relation between free variable (reliability, responsive, guarantee, empathy and is extant) to variable is not free (satisfaction of cunsumer), while coefficient value of determiners (R2) 0,511 or 51,10%, meaning 51,10% variation of satisfaction of consumer can be explained by variation from is fifth of free variable (reliability, responsive, guarantee, empathy and is extant), while 51,10% explained by other variable which not check in research.